ACUTE RESPIRATORY DISTRESS SYNDROME AFTER TRAUMATIC BRAIN INJURY: TIMING, ASSOCIATED CLINICAL FACTORS, MANAGEMENT, AND OUTCOMES IN A MOROCCAN INTENSIVE CARE UNIT - Asmae Hajji; Derkaoui Ali; Ibrahim Bechri; Abdelkarim Shimi; Mohammed Khatouf (World Journal of Advanced Research and Reviews, 2026)
Background: Acute respiratory distress syndrome (ARDS) is an important extracranial complication of traumatic brain injury (TBI), but its timing, associated clinical factors, and management are difficult to disentangle from the effects of prolonged mechanical ventilation and neurocritical illness. Data from North African intensive care units are limited. We aimed to describe the incidence, timing, associated clinical factors, management, and short-term outcomes of ARDS occurring after TBI in a Moroccan university intensive care unit. Methods: We conducted a retrospective, single-center observational study of patients older than 15 years admitted with head trauma to the anesthesiology and intensive care unit of Hassan II University Hospital, Fez, Morocco, from January 2020 through December 2022. Patients were included if they developed ARDS according to the Berlin definition during the ICU stay. Patients with respiratory failure attributed to a cardiac origin were excluded. Patients with confirmed or suspected SARS-CoV-2 infection were managed in a dedicated COVID-19 unit separate from Unit A1 and therefore were not part of the source population analyzed. Clinical, radiological, therapeutic, and outcome data were collected from hospital records and analyzed descriptively. Results: Among 2,217 ICU admissions, 270 involved head trauma and 45 patients developed ARDS (16.7% of head-trauma admissions, 95% CI 12.7-21.6; 2.0% of all ICU admissions). Mean age was 34.2 years and 84.4% were male. ARDS developed a mean of 7.2 days after trauma and 6.4 days after ICU admission. Mean PaO2/FiO2 at diagnosis was 156 mmHg; ARDS was mild in 20.0%, moderate in 57.8%, and severe in 22.2%. Frequently documented associated clinical factors were ventilator-associated pneumonia (75.6%), sepsis or septic shock (53.3%), associated chest trauma (35.6%), aspiration (17.8%), and pancreatitis (11.1%); categories overlapped. Mean duration of mechanical ventilation was 17.6 days. Inhaled nitric oxide was used in 37.8% and prone positioning in 28.9%. ICU mortality was 66.7%; 24.4% survived with documented severe neurological and/or cognitive impairment at ICU discharge and 8.9% survived without documented severe neurological/cognitive impairment. Conclusions: In this cohort, ARDS after TBI was usually diagnosed several days into the ICU course and occurred in a population with a high burden of nosocomial infection, particularly ventilator-associated pneumonia. ICU mortality was very high. These findings highlight the complexity of brain-lung interactions after TBI and the importance of preventing respiratory and infectious complications during prolonged neurocritical care.